The formation of professional competence of students in the study of logic (Pedagogy of Higher and Secondary Education, 2012)
Kozachenko N. The formation of professional competence of students in the study of logic.The article discusses the relation between professional competence and logical culture. The author formulates the main characteristics of logical culture of the students and pupils in the context ofcompetence-based approach.
Keywords: professional competence; logical culture; rationality; effectiveness; formalization